Linguistic Characteristics In The Research Background And Problem Statement In The Doctoral Thesis Of Arabic EFL Students In Malaysia - Al Jarrah, Monther; A Kadhim, Kais (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study explores the linguistic features within the move structures of the research background and problem statement sections in Chapter One of PhD theses written by Arab students in Malaysia. The analysis focuses on four key language elements: verb tense, modality, voice (active and passive), and personal pronouns. A corpus of 30 theses was analyzed to determine common linguistic patterns, revealing significant insights into the language choices of these academic writers. The study employs concordance and hand-tagged analysis to examine verb tense and voice, with manual verification for modality and personal pronouns to ensure accuracy. Eight distinct verb tenses were identified, with the present simple tense being the most frequently used, representing 55.30% of the total instances. This indicates a preference for focusing on current knowledge and ongoing research. In contrast, the past simple and future simple tenses were used to describe past methodologies and future implications, respectively. Modal auxiliaries play a crucial role in conveying sentiments and opinions. The study identified seven modal verbs, with 'can' being the most commonly used, suggesting a focus on possibility over obligation. The analysis of voice patterns revealed a higher occurrence of active voice (79.66%), especially in moves that conveyed up-to-date knowledge. In contrast, passive voice was more common in methodological descriptions, indicating a focus on the actions or subjects rather than the actors. The study also examined the usage of personal pronouns, finding a higher frequency of third-person pronouns, suggesting a more objective narrative style. These findings offer valuable insights into the linguistic choices of Arab EFL students in academic writing, providing a deeper understanding of their communicative intentions and alignment with academic discourse conventions. The results can guide future research on linguistic patterns in academic writing and help educators support EFL students in improving their writing skills.